Quality of persuasive analogical arguments: results of an educational intervention in university students - Gómez, Ana Elia (2024)
Introduction. Previous studies on analogical argumentation have demonstrated that when individuals attempt to persuade, they often compare the current situation to a known one, presenting a complete causal structure (i.e., cause and effect). These types of analogies are perceived as more persuasive by the listener. However, there is a notable absence of research aimed at promoting argumentative skills based on analogies. Objective. This study aimed to evaluate an educational intervention designed to enhance the quality of persuasive analogical arguments. Method. An experimental study with a pre-test, post-test control group design was conducted, where participants were asked to generate analogies to reassure a potential interlocutor. A total of 207 university students were randomly assigned to two groups. While the control group received a general presentation on analogical reasoning, the experimental group underwent the educational intervention, which focused on teaching participants to construct analogical arguments with a complete structure. Results. The intervention results for the experimental group indicated a statistically significant increase in the generation of analogies with a complete structure in the post-test, compared to the control group, t(204) = 5.02, p < .001, d = .70. Discussion. The intervention proved effective for its intended purpose and demonstrated practical applicability due to its low demands on time and resources while reaching a large number of participants. Additionally, this approach is anticipated to be beneficial for those seeking to improve argumentation skills in educational settings.